2015
DOI: 10.1002/em.21988
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of primary human gliomas triggers dynamic and aggressive survival responses involving microvesicle signaling

Abstract: Malignant gliomas are heterogeneous populations of dynamically interacting cells. Genomic and transcriptional changes define this cellular hierarchy and allow certain tumor cells to co-opt metabolic machinery and adopt gene expression profiles that promote cellular reprogramming. Resultant expansion of privileged subpopulations can then rapidly adapt to microenvironmental stress that ultimately influence tumor response to therapeutic intervention. In this study, primary gliomas were subjected to acute or chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…We then carried out a study of the radiation effect on molecular changes measured by gelatin zymography and AqRT-PCR, and on redox status by fluorescence activated cell sorting. In our previous study of radiation effects on glioma cells, we found that the extracellular level of MMP2 was upregulated by radiation [ 5 ]. Here, again we found that the high-MMP2-expressing cells of 51B had increased MMP2 1-3 weeks following both acute and chronic IR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then carried out a study of the radiation effect on molecular changes measured by gelatin zymography and AqRT-PCR, and on redox status by fluorescence activated cell sorting. In our previous study of radiation effects on glioma cells, we found that the extracellular level of MMP2 was upregulated by radiation [ 5 ]. Here, again we found that the high-MMP2-expressing cells of 51B had increased MMP2 1-3 weeks following both acute and chronic IR.…”
Section: Resultsmentioning
confidence: 99%
“…Significant evidence points to the intra-tumoral heterogeneity of GBM as a major confounding factor for therapy, as plasticity of the subpopulation phenotypes, driven by evolving selective pressures within the tumor microenvironment, promote treatment resistance and tumor recurrence. This is supported by much of our past work demonstrating that clinically relevant irradiation (IR) paradigms were associated with increased oxidative stress, radio-resistance, cellular reprogramming and invasive behavior, of which the latter could be mediated by radiation-induced macrovesicles [ 4 , 5 ]. Similarly, work by ourselves and others has also substantiated the importance of EGFR amplification in GBM, either as chromosomal 7 polysomy or as double minute chromosomes (DMs) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 85%
“…In addition to the effect of SALL2 on tumour growth, we studied the effect of SALL2 on tumour migration and invasion. SALL2 interacts with other transcription factors to participate in cell reprogramming and inhibition of the migration and invasion of malignant glioma cells following ionising radiation [ 36 ]. Furthermore, SALL4 is involved in invasion of different tissues by various epithelial cancers, such as colon villous epithelial cancer and prostate cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their cargo encompasses proteins, RNA, and lipids specific for the cell of origin (3)(4)(5). In the neoplastic setting, they induce tumor progression and infiltration, sustain neoangiogenesis, inhibit immune response, and lead to chemo/radio-resistance (3,(6)(7)(8)(9)(10)(11)(12). Interestingly, extracellular vesicles can be used as circulating biomarkers because they can be easily isolated from bloodstream, urine, cerebrospinal, ascitic, amniotic, and seminal fluid (4).…”
Section: Introductionmentioning
confidence: 99%